AN UNCERTAIN CLIMATE IN RISKY TIMES: HOW OCCUPATION BECAME LIKE THE RAIN IN POST-OSLO PALESTINE. (5th September 2018) - Stamatopoulou-Robbins, Sophia
Abstract: Recent Palestinian Authority (PA) initiatives to help Palestine adapt to climate change help shine light on the role that climate uncertainties play in how political futures can be represented. UN-led adaptation has occasioned opportunities for new networks of actors to make claims about Palestinian futures and to perform PA readiness for statehood. These actors weigh scientific uncertainties about climate against uncertainties over if and when settler colonialism in Palestine will end. How they do so matters because it is the foundation of requests for capital that could be translated into some of the most important institutions and infrastructures of Palestinian governance over the next several years, including those that provide Palestinians with access to water. It also matters because it constitutes the image with which PA officials represent what needs to be "fixed" in Palestine in important international forums such as the UN. Climate change adaptation is a new approach to the management of uncertain environmental futures. This analysis offers insight into how this approach shapes and is shaped by practices of statecraft in places marked by the volatilities of war, economic crisis, and occupation.